2018
DOI: 10.1080/10717544.2018.1464082
|View full text |Cite
|
Sign up to set email alerts
|

Glioma targeting peptide modified apoferritin nanocage

Abstract: Therapeutic outcome for the treatment of glioma was often limited due to the non-targeted nature of drugs and the physiological barriers, including the blood-brain barrier (BBB) and the blood-brain tumor barrier (BBTB). An ideal glioma-targeted delivery system must be sufficiently potent to cross the BBB and BBTB and then target glioma cells with adequate optimized physiochemical properties and biocompatibility. However, it is an enormous challenge to the researchers to engineer the above-mentioned features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Although these acoustically responsive nanoplatforms have been reported to exhibit good tumor diagnosis and treatment integration capabilities, the biocompatibility of nanocarriers is still a concern for clinical transformation. In recent years, iron-free ferritin nanocages have been widely used as drug delivery vehicles because they are endogenous proteins and have significant pH sensitivity [25][26][27]. They can decompose in acidic environments and reassemble in alkaline environments.…”
Section: Introductionmentioning
confidence: 99%
“…Although these acoustically responsive nanoplatforms have been reported to exhibit good tumor diagnosis and treatment integration capabilities, the biocompatibility of nanocarriers is still a concern for clinical transformation. In recent years, iron-free ferritin nanocages have been widely used as drug delivery vehicles because they are endogenous proteins and have significant pH sensitivity [25][26][27]. They can decompose in acidic environments and reassemble in alkaline environments.…”
Section: Introductionmentioning
confidence: 99%
“…A dual-targeted delivery system (GKRK-APO) made of APO and GKRK peptide ligand, increases the specific targeting to brain endothelial cells and glioma cells and displayed higher glioma localization. Based on the results of the experiments, it has been demonstrated that GKRK-APO loaded with VCR efficiently overcame multiple barriers (e.g., BBB and BBTB) and showed an effective anti-glioma effect in vitro and in vivo [ 128 ]. Another study relates to the Pep-1&borneol-bifunctionalized CMS-loaded micelles (Pep1/Bor/CMS-M) was able to target interleukin-13 receptor overexpressed glioma and penetrate BBB.…”
Section: Application and Clinical Trials Of Nanocarrier-based Thermentioning
confidence: 99%
“…Advancements in the comprehension of molecular, cellular and genetic anomalies of various tumors have enabled the development of the "Atlas of Genetics and Cytogenetics in Oncology and Haematology", a database listing several genes and proteins that are relevant for different types of cancer, including diffuse glioma. Some of these have been investigated as potential targets for small molecules or peptide vaccines, while others were specifically addressed with peptidic agents [36][37][38][39]. Peptidic molecules can be used both as monotherapy as well as in combination with standard anti-cancer drugs.…”
Section: Molecular Targets For Peptide-based Treatments Of Astrocytomasmentioning
confidence: 99%